Cover Image. (1st May 2019) - Guo, Yang; Li, Jin‐Ming; Xiang, Yu; Li, Yang‐You; Huang, Jing; Deng, Xian‐Zhong; Yang, Zheng‐Wei
Abstract : The cover image is based on the Original Article Quantitative (stereological) study of the epididymis and seminal vesicle in the rat from young to old by Yang Guo et al., DOI:10.1111/and.13247 .